Analisis Profil Pelajar Pancasila Dalam Buku Cerita Bergambar Keteladanan Potre Koneng - Putri, Estin Muharromah Pratiwi; Rosyadi, Dede; Fajrin, Nilamsari Damayanti (Yayasan Arrahman Nahdlatul Wathan, 2024)
In this era of rapid globalization, it is causing a character and moral crisis. To overcome this problem, the government is currently starting to implement an independent curriculum, which in its implementation includes a Pancasila Student Profile to instill student character based on Pancasila values. To apply it in a fun learning process, learning media is needed that can support the cultivation of the Pancasila Student Profile. One of them is by using picture storybook media. However, in selecting the media you also need to pay attention to whether there are values in the Pancasila Student Profile or not. Therefore, in this study the researcher will analyze the values in the Pancasila Student Profile in the picture story book